Development and validation of a high‐throughput online solid‐phase extraction–liquid chromatography–tandem mass spectrometry method for the detection of gonyautoxins 1&4 and gonyautoxins 2&3 in human urine. (14th March 2017) - Coleman, Rebecca; Lemire, Sharon W.; Bragg, William; Garrett, Alaine; Ojeda‐Torres, Geovannie; Wharton, Rebekah; Hamelin, Elizabeth; Thomas, Jerry; Johnson, Rudolph C.
Abstract: Paralytic shellfish toxins (PSTs), including gonyautoxins and saxitoxins, are produced by multiple species of microalgae and dinoflagellates, and are bioaccumulated by shellfish and other animals. Human exposure to PSTs typically occurs through ingestion of recreationally harvested contaminated shellfish and results in nonspecific symptomology. Confirmation of exposure to PSTs has often relied on the measurement of saxitoxin, the most toxic congener; however, gonyautoxins (GTXs), the sulfated carbamate derivatives of saxitoxin, may be present in shellfish at higher concentrations. To improve identification of PST exposures, our group has developed an online solid phase extraction hydrophilic interaction liquid chromatography method to identify GTX1–4 in human urine with tandem mass spectrometry. The reportable range varied for each analyte, with all falling within 0.899 and 250 ng/mL in urine with precision <15% and >85% accuracy as determined for all quality control samples. This new online method quantitates GTX1–4 following exposures to PSTs, supporting the work of public health authorities.